2017
DOI: 10.1080/15389588.2017.1322203
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motorcycle-related injuries and deaths after mandatory motorcycle helmet law in a district of Vietnam

Abstract: Rates of head injuries and deaths among motorcycle riders decreased significantly after implementation of the mandatory helmet law in Vietnam. To further examine the impact of the motorcycle helmet law, including compliance and helmet quality, further emphasis should be placed on gathering helmet use data from injured motorcyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
5
22
0
1
Order By: Relevance
“…20,41 In terms of primary prevention of traumatic brain injury, multiple in-vestigators have found interventions aimed at increasing helmet use successful. 19,32,36 Among practices aimed at improving advanced, technical capacity, the Direction of Healthcare Activities (DOHA) program has been developed over the past 50 years to accelerate the transfer of technical skills to community hospitals. While these reforms are considered anecdotally successful and have been described as a model for nations with limited healthcare resources, our search did not detect any reliable systematic assessment of the impact of DOHA activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,41 In terms of primary prevention of traumatic brain injury, multiple in-vestigators have found interventions aimed at increasing helmet use successful. 19,32,36 Among practices aimed at improving advanced, technical capacity, the Direction of Healthcare Activities (DOHA) program has been developed over the past 50 years to accelerate the transfer of technical skills to community hospitals. While these reforms are considered anecdotally successful and have been described as a model for nations with limited healthcare resources, our search did not detect any reliable systematic assessment of the impact of DOHA activities.…”
Section: Resultsmentioning
confidence: 99%
“…24 A high prevalence of motorized scooters has resulted in a disproportionate rate of traumatic brain injury following motor vehicle accidents (previously estimated at roughly 70% of all road injuries). 19,21 As studies have shown superior outcomes with improved neurosurgical and neurocritical care, this compels additional investments in such neurosurgical capital. 11,28,39 Similar to the rest of the world, low-back and neck pain is the number one cause of disability in Vietnam (http://www.healthdata.org/vietnam); its prevalence has increased 29.4% since 2005.…”
mentioning
confidence: 99%
“…First, in measuring outcome in terms of PYLLs, the burden of mortality could also take into account the age of death in addition to the number of deaths, commonly reported in previous studies. 6 18 34 Second, the study reported the changes in the PYLLs before and after the helmet law and the trend of PYLL over 6 months following the effective date of the law. Third, the study examined the impacts of the helmet law across all provinces and then pooled estimates of the impact at the national level; whereas the previous work did the evaluation at the sample locations but not throughout the country.…”
Section: Discussionmentioning
confidence: 99%
“…17 Ha et al 6 found that motorcycle-related injuries and deaths reduced by 47% and 31%, respectively, in a district in Vietnam after the implementation of the 2007 mandatory helmet law. 6 Olson et al indicated that the introduction of helmet policy was likely preventing 2200 deaths and 29 000 head injuries, saved US$18 million in acute care costs and averted US$31 million in income losses in Vietnam. 18 While prior studies provided valuable information on the effect of the 2007 helmet law, the temporal trend of changes in traffic injuries following the effective date of the law and the variability of changes across provinces has been unknown.…”
Section: Introductionmentioning
confidence: 99%
“…La mayor gravedad encontrada entre los conductores que no usaban casco en el momento del accidente concuerda con lo encontrado en numerosas investigaciones que señalan como la utilización del casco reduce el riesgo de lesiones en la cabeza y la cara, así como de fallecimiento en caso de accidente (Ha et al, 2018;Moskal, Martin & Laumon, 2008;Rice et al, 2016).…”
Section: Discussionunclassified